Pengaruh Penggunaan Fitur Shopee Games terhadap Customer Engagement pada Kalangan Mahasiswa di Kota Malang - Molyo, Priyo Dari; Yulistiowati, Irma Mufita; Zulhilmi, Fajar (Jurnal Nomosleca, 2021)
In the midst of the increasing number of people to fulfill their needs by shopping online, there are dozens of e-commerce providers that offer the same service, namely accommodating sellers to be able to sell online, this is a challenge for e-commerce players to scramble for attention so that consumers choose e- commerce as a "subscription shop" and changing from consumers to customers. Shopee as one of the e-commerce comes with different things, namely the shoope games feature, the shopee games feature is a feature in which consumers can play interesting games and get prizes or rewards from their efforts to play these games, the prizes obtained can help make it easier In terms of shopping, the examples are discount vouchers and free shipping, in certain events the prizes provided are not in the form of a car or umrah. The shop feature is made so that consumers feel at home for a long time in the shop application, and there will be customer engagement or an attachment relationship with the customer so that customer loyalty will emerge. The purpose of this study was to determine the effect of Shopee Games features on Customer Engagement among students in Malang City. By using this type of quantitative research with a descriptive approach, the sampling technique used in this study was purposive sampling, the sample was taken as many as 35 respondents, and this study used simple regression as data analysis and also hypothesized. The results obtained by the author is the Shopee Games feature on Customer Engagement among Students in Malang City. So it can be concluded that testing the hypothesis which states that the influence of the Shopee games feature on the variable customer engagement among students in Malang is acceptable. Keywords:Â E-Commerce, Game Fitures, Costumer EngagementDOI :Â https://doi.org/10.26905/nomosleca.v7i1.5541